Religious Freedom, the Sex Discrimination Act, and Section 109: A Surrejoinder to Butler - Neil Foster (Australian Journal of Law & Religion)
In a previous article, I argued that section 109 of the Australian Constitution would prohibit State laws imposing different and more demanding requirements on religious schools than requirements imposed by Federal laws. In a subsequent rejoinder, Nicholas Butler reached the opposite conclusion. In this surrejoinder, I return to a discussion of the High Court’s jurisprudence on section 109 and conclude that Butler’s critique is well-written but ultimately unconvincing.